Serration Design Methodology for Wind Turbine Noise Reduction. Issue 2 (September 2016) - Mathew, J; Singh, A; Madsen, J; Arce León, C
Abstract: Trailing edge serrations are today an established method to reduce the aeroacoustic noise from wind turbine blades. In this paper, a brief introduction to the aerodynamic and acoustic design procedure used at LM Wind Power is given. Early field tests on serrations, retrofitted to the turbine blades, gave preliminary indication of their noise reduction potential. However, a multitude of challenges stand in the way of any proof of concept and a viable commercial product. LM undertook a methodical test and validation procedure to understand the impact of design parameters on serration performance, and quantify the uncertainties associated with the proposed designs. Aerodynamic and acoustic validation tests were carried out in number of wind tunnel facilities. Models were written to predict the aerodynamic, acoustic and structural performance of the serrations. LM serration designs have evolved over the period of time to address constraints imposed by aero performance, structural reliability, manufacturing and installation. The latest LM serration offering was tested in the field on three different wind turbines. A consistent noise reduction in excess of 1.5 dB was achieved in the field for all three turbines.